2016
DOI: 10.1007/s10973-016-5985-6
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and kinetic analyses on Michael addition reaction of acrylic acid

Abstract: The purpose of this study is to obtain a better understanding of Michael addition reaction (MAR) which may induce runaway polymerization of acrylic acid. The heat of MAR was measured using a C80 Calvet-type heat flux calorimeter, and products of MAR were revealed by gel permeation chromatography. The reaction rate constant of MAR was obtained from kinetic analysis. In high-sensitivity calorimetry, a low rate of heat release due to MAR was detected. The heat of MAR was 109 J g -1 and conversion of acrylic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…It is known that acrylic acid can oligomerize via carboxylic-alkene Michael addition. 13 This is especially prevalent at elevated temperatures in the presence of water and would be a likely explanation for the lower acid number. GC-MS experiments, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that acrylic acid can oligomerize via carboxylic-alkene Michael addition. 13 This is especially prevalent at elevated temperatures in the presence of water and would be a likely explanation for the lower acid number. GC-MS experiments, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Acrylic acid is known to polymerize through a Michael addition reaction, 43 which generates thermal energy and selfaccelerates polymerization. 44,45 It has been reported that alkali metal acrylates, alkali-earth metal acrylates, and transition metal acrylates show thermally induced solid-state polymerization. 46,47 Considering these facts, the thermal Fig.…”
Section: Solid-state Thermal Polymerization Of Acrylates Intercalated In Layered Metal Hydroxidesmentioning
confidence: 99%
“…In order to prevent such accidents, it is necessary to understand the hazards of mixing chemicals using the mixing hazard evaluation method. In general, thermal hazard is usually evaluated with milligram or gram scale sample using heat flow calorimeter [3,4] or accelerating rate calorimeter [5]. In mixing hazard evaluation, screening tests are conducted by observing bubble generation and measuring the temperature rise using a test-tube or beaker [6].…”
Section: Introductionmentioning
confidence: 99%